A Cloud-Based Architecture with embeded Pragmatics Renderer for Ubiquitous and Cloud Manufacturing - Ferreira, Luís (2017)
The paper presents a Cloud-based architecture for Ubiquitous and Cloud Manufacturing as a multilayer communicational architecture designated as the Communicational Architecture. It is characterised as (a) rich client interfaces (Rich Internet Application) with sufficient interaction to allow user agility and competence, (b) multimodal, for multiple client device classes support and (c) communicational to allow pragmatics, where human-to-human real interaction is completely supported. The main innovative part of this architecture is sustained by a semiotic framework organised on three main logical levels: (a) device level, which allows the user ‘to use’ pragmatics with the system, (b) application level which results for a set of tools which allows users pragmatics-based interaction and (c) application server level that implements the Pragmatics renderer, a pragmatics supporting engine that supports all pragmatics services. The Pragmatics renderer works as a communication enabler, and consists of a set of integrated collaboration technology that makes the bridge between the user/devices and the ‘system’. A federated or community cloud is developed using a particular cloud RESTful Application Programming Interface that supports (cloud) services registration, composition and governance (pragmatics services behaves as SaaS in the cloud).